Effect of light pollution on self-reported sleep quality and its components: Comparative assessment among healthy adult populations in a rural and an Urban area of West Bengal, India - Arista Lahiri; Arup Chakraborty; Amal Kumar Sinha Roy; Urmila Dasgupta; Krishnadas Bhattacharyya (Wolters Kluwer Medknow Publications, 2020)
Background: Light pollution is inappropriate or excessive use of artificial light. Nighttime sky radiance is an effective measure to study its effects on individual sleep quality. Objectives: The study is aimed to measure the effect of light pollution on the sleep quality and compare among people residing in selected rural and urban areas of West Bengal, India. Methods: A comparative cross-sectional study was conducted during September-October 2018 in 10 villages of Barasat II block and 10 wards of Kolkata Municipal Corporation. Two hundred and sixty-three participants from urban and 249 participants from rural areas were selected through multi-stage sampling. Data regarding sleep quality and other selected factors were geotagged along with the radiance data. Multi-level linear regression models were built. Results: The mean age of the participants from rural and urban areas were respectively 37.65 (±10.77) years and 38.10 (±11.02) years. Gender-wise the participants were distributed almost evenly in urban and rural areas. Among the urban and rural population, the observed mean global Pittsburgh Sleep Quality Index scores were 12.63 (±3.04) and 9.23 (±2.27), respectively. Poorer sleep quality was observed to be statistically significant with increasing level of exposure. Multi-level models show that, at an exposure of >40.0 nW/cm2/sr the adjusted coefficient was 11.52 (95% confidence interval [CI]: 9.65, 13.40) in the overall model and 12.84 (95% CI: 12.31, 13.37) for urban participants. Conclusion: The disturbance in sleep is associated with higher levels of night-time radiance of the sky strongly observed among the urban population.